PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, PERILAKU BELAJAR, DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI IFRS (Studi Empiris Tingkat Pemahaman International Financial Reporting Standards Pada Mahasiswa Universitas Stikubank) - Aprillia Hasta Wulandari, 12.05.52.0088; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the emotional intelligence, spiritual intelligence, learning behavior, and interest in learning to the level of understanding of IFRS accounting. The population in this research is the study of accounting S1 students enrolled University Stikubank (Unisbank) Semarang. Sampling was done by convenience sampling technique. The number of samples obtained as many as 41 people from the number of students enrolled in the University Stikubank (Unisbank) Semarang. Data analysis techniques used in this research is the technique of multiple linear regression analysis. The results showed that the variables of emotional intelligence, spiritual intelligence, and behavior learning does not affect the level of understanding of IFRS accounting, while interest in learning affect the level of understanding of IFRS accounting.Â  Â Keywords: Emotional Intelligence, Spiritual Intelligence, Learning Behavior, Interests Learning, Understanding of IFRS